Characterization of 150 μm thick silicon microstrip prototype for the FOOT experiment. (1st December 2022) - Alexandrov, Andrey; Alpat, Behcet; Ambrosi, Giovanni; Argirò, Stefano; Arteche, Diaz Raul; Barbanera, Mattia; Bartosik, Nazar; Battistoni, Giuseppe; Belcari, Nicola; Bellinzona, Elettra; Biondi, Silvia; Bisogni, Maria Giuseppina; et al.
Abstract: The goals of the FOOT (FragmentatiOn Of Target) experiment are to measure the proton double differential fragmentation cross-section on H, C, O targets at beam energies of interest for hadrontherapy (50–250 MeV for protons and 50–400 MeV/u for carbon ions), and also at higher energy, up to 1 GeV/u for radioprotection in space. Given the short range of the fragments, an inverse kinematic approach has been chosen, requiring precise tracking capabilities for charged particles. One of the subsystems designed for the experiment will be the MSD (Microstrip Silicon Detector), consisting of three x-y measurement planes, each one made by two single sided silicon microstrip sensors. In this document, we will present a detailed description of the first MSD prototype assembly, developed by INFN Perugia group and the subsequent characterization of the detector performance. The prototype is a wide area (∼ 100 cm 2 ) single sensor, 150 μm thick to reduce material budget and fragmentation probability along the beam path, with 50 μm strip pitch and 2 floating strip readout approach. The pitch adapter to connect strips with the readout channels of the ASIC has been implemented directly on the silicon surface. Beside the interest for the FOOT experiment, the results in terms of cluster signal, signal-to-noise ratio, dynamic range of the readout chips, as well as long-term stability studies in terms of noise, are relevant also for other experiments where the use of thin sensors is crucial.